Stringent Road Safety Laws; Need of the Hour to Stop the Homicides on Indian Roads: A Regulatory Perspective (Medico Legal Update, 2021)
Indian roads are deemed to be the most dangerous, considering the number of annual fatalities, whichtouched 151,113 in the year 2019, the highest in the world. Causes ranging from poorly designed roads,tardy enforcement of traffic rules, delay in giving medical assistance, ill equipped hospitals, refusal oftreatment by hospitals, all contribute to this unenviable predicament. A lax regulatory environment withminor penalties, has accentuated the crisis. Having held the pivotal position amongst 199 countries, there isa dire need for concrete action by Government. While 2,211,439 road accidents in the US in the year 2016took away 37,461 lives,a relatively lower number of 480,652 accidents snuffed out 150,785 lives in India.Creating comparable safety levels could take decades for a developing country. But with the country’s shareconstituting about 11% of road accident casualties worldwide and the estimated social cost hovering around$58 billion, the problem begs for an immediate fix. Tightening regulations would be a practical solution forboth short and long-term gains. Enough deterrents need to be put in rules governing road safety; the MotorVehicles Act to ensure defensive driving. This paper examines how certain loopholes need to be plugged inthe new Motor Vehicles Act 2019 to achieve the higher goal of road safety